2012
DOI: 10.1371/journal.pone.0043170
|View full text |Cite
|
Sign up to set email alerts
|

Modern Lineages of Mycobacterium tuberculosis Exhibit Lineage-Specific Patterns of Growth and Cytokine Induction in Human Monocyte-Derived Macrophages

Abstract: BackgroundStrains of Mycobacterium tuberculosis vary in virulence. Strains that have caused outbreaks in the United States and United Kingdom have been shown to subvert the innate immune response as a potential immune evasion mechanism. There is, however, little information available as to whether these patterns of immune subversion are features of individual strains or characteristic of broad clonal lineages of M. tuberculosis.MethodsStrains from two major modern lineages (lineage 2 [East-Asian] and lineage 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 41 publications
8
59
0
Order By: Relevance
“…in their US patient population and those found in our French cohort: 87.0 vs. 80.0%, 86.2 vs. 75.3%, 77.4 vs. 64.9% and 65.7 and 50.0% for the East Asian/Beijing, Euro-American, Indo-Oceanic and East African-Indian lineages, respectively (R 2  = 0.99, P  = 0.006). Taken collectively, these results bring additional support to the hypothesis of MTBC lineage-specific adaptations impacting on disease14446474849, including the ability to generate active pulmonary TB as a major driving force of MTBC population dynamics4450.…”
Section: Discussionsupporting
confidence: 60%
“…in their US patient population and those found in our French cohort: 87.0 vs. 80.0%, 86.2 vs. 75.3%, 77.4 vs. 64.9% and 65.7 and 50.0% for the East Asian/Beijing, Euro-American, Indo-Oceanic and East African-Indian lineages, respectively (R 2  = 0.99, P  = 0.006). Taken collectively, these results bring additional support to the hypothesis of MTBC lineage-specific adaptations impacting on disease14446474849, including the ability to generate active pulmonary TB as a major driving force of MTBC population dynamics4450.…”
Section: Discussionsupporting
confidence: 60%
“…We considered n ¼ 186 patients, n mix ¼ 35 of whom are detected with mixed infection, as in Warren et al (2004). The values for the growth rates are in line with the estimations in Sarkar et al (2012). The raw estimate from the data would indicate a mixed infection prevalence of approximately n mix =n ¼ 19%, corresponding to ρ ¼ 0:19, however we observe that, even in the most optimistic scenario (green dashed line) the posterior ρ is higher that is 0.19 with probability 0.9 and has mean over 0.23.…”
Section: Random Variablesupporting
confidence: 55%
“…However, the second scenario was possible, because cytokines secreted by lymphocytes could have changed the gene expression profile of macrophages. Furthermore, different strains of M. bovis possess different growth patterns and cytokine induction abilities on macrophages (Sarkar et al, 2012;Tanveer et al, 2009), which might also contributed to the differences we have observed.…”
Section: Discussionmentioning
confidence: 88%